2010
DOI: 10.1051/0004-6361/201015504
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared spectroscopy ofSpitzer-selected ultra-luminous starbursts atz  ~ 2

Abstract: Context. Spitzer's wide-field surveys and followup capabilities have allowed a new breakthrough in mid-IR spectroscopy up to redshifts ≥2, especially for 24 μm detected sources. Aims. We want to study the mid-infrared properties and the starburst and AGN contributions, of 24 μm sources at z ∼ 2, through analysis of mid-infrared spectra combined with millimeter, radio, and infrared photometry. Mid-infrared spectroscopy allows us to recover accurate redshifts. Methods. A complete sample of 16 Spitzer-selected so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 84 publications
(257 reference statements)
7
31
0
Order By: Relevance
“…It also indicates that the low-redshift SFR calibration based on PAH luminosities is appropriate to use for high-redshift ULIRGs, even if it is not appropriate for low-redshift ULIRGs, consistent with other recent studies that have demonstrated this result (i.e., Rujopakarn et al 2013). However, at even higher total IR luminosities (L L 3 10 IR 12  ), there is evidence that the L PAH /L IR ratio declines for the high-redshift samples (e.g., Fiolet et al 2010). We fit this trend seen in Figure 12 as a broken powerlaw and derive a linear fit above this luminosity using the high-redshift samples of Pope et al (2013) …”
Section: The Validity Of Pah-estimated Sfrs For Very Highsupporting
confidence: 84%
“…It also indicates that the low-redshift SFR calibration based on PAH luminosities is appropriate to use for high-redshift ULIRGs, even if it is not appropriate for low-redshift ULIRGs, consistent with other recent studies that have demonstrated this result (i.e., Rujopakarn et al 2013). However, at even higher total IR luminosities (L L 3 10 IR 12  ), there is evidence that the L PAH /L IR ratio declines for the high-redshift samples (e.g., Fiolet et al 2010). We fit this trend seen in Figure 12 as a broken powerlaw and derive a linear fit above this luminosity using the high-redshift samples of Pope et al (2013) …”
Section: The Validity Of Pah-estimated Sfrs For Very Highsupporting
confidence: 84%
“…We note that the predominately radio-quiet Higdon et al (2006) sample of ULIRGs (0.02 < z < 0.93) and the Schweitzer et al (2006) sample of QSOs (z < 0.3) have H 2 -to-PAH luminosity ratios significantly higher than the SINGS star-forming galaxies. Although their H 2 -to-PAH luminosity ratios are compatible with the range of ratios predicted by PDR models, other studies (based on extinction or H 2 -to-CO line ratios) suggest that additional sources of H 2 excitation (other than UV photon heating) are required to explain the H 2 emission (e.g., shocks; see Zakamska 2010;Fiolet et al 2010).…”
Section: Which Dominant Mechanism Powers the H 2 Emission?supporting
confidence: 61%
“…Desai et al (2008) and Fiolet et al (2010) addresses the redshift distribution of 24µm-selected sources by confirming a set of >400 sources spectroscopically out of ∼600 targeted. They find that the redshift distribution of 24µm galaxies brighter than 300 µJy peaks at z ∼ 0.3 with a possible second peak at z ∼ 0.9 and a tail of galaxies detected out to z ∼ 4.5.…”
Section: Redshift Distributions Of 24 µM Selected Dsfg Populationsmentioning
confidence: 99%